Spatial Inequality Analysis of Creative Economy Development in Kotatua Jakarta Cultural Heritage Area: A Transdisciplinary Governance Approach - Roby Dwiputra; Galih Hutama Putra; Kanika Prinka Pramesti (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2026)
This study analyzes the spatial inequality in the development of the creative economy within the Kotatua Jakarta Cultural Heritage Area. Creative economy activities remain heavily concentrated in the core zone of Taman Fatahillah, while peripheral areas such as Kali Besar Barat and Pecah Kulit are relatively quiet, with many cultural heritage buildings left underutilized and abandoned. This condition contrasts sharply with the more inclusive revitalization model implemented in Semarang Old Town. The research employs a transdisciplinary approach based on literature review, qualitative descriptive analysis, and transdisciplinary SWOT analysis. The theoretical framework draws upon Mode 2 knowledge production and transdisciplinarity as the methodological foundation, wicked problems theory to frame the complexity of the issue, and the concepts of cultural heritage-based creative economy and creative city as the contextual application. The findings indicate that top-down approaches contribute to fragmented development, whereas cross-actor knowledge co-production holds significant potential to promote more equitable and sustainable revitalization. This study offers novelty by integrating recent regulatory frameworks with creative city principles within a transdisciplinary governance approach, and generates actionable policy recommendations, including the development of community-based heritage incubators.